Seawater-based delayed cross-linking agent and seawater-based ultralow-concentration guanidine gum fracturing fluid
By using seawater-based delayed crosslinking agent and crosslinking synergist in the guanidine glue fracturing fluid, the problems of low viscosity and poor sand carryingability at high temperatures are solved, which significantly improves crosslinking efficiency and temperature resistance, and reduces the cost and damage to the reservoir by the residue.
Patent Information
- Application Number
- CN202311213641.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing guanidine glue fracturing liquid has low viscosity and poor sand carrying properties at high temperatures. High-priced metal ions affect the temperature resistance and cross-linking strength of guanidine glue when dispensing liquids, resulting in poor fracturing effect and high cost.
Using seawater-based delayed crosslinking agent, specifically polyurethane boron crosslinking agent, the preparation method is used to react compounds such as ethylene glycol, n-butanol, boric acid, tetravinyl pentamine and polyol at a specific molar ratio to form a crosslinking agent with multiple crosslinking sites, and combined with seawater-based crosslinking synergists and plant gel thickening agents, seawater-based ultra-low concentration guanidine gel fracturing liquid is prepared.
The crosslinking efficiency of guanidine glue and the viscoelasticity and rheology of frozen glue are significantly improved, the problems of low viscosity and poor sand carrying properties at high temperatures are reduced, the usage and residue content of guanidine glue are reduced, the cost of fracturing fluid is reduced, and good temperature resistance is maintained under seawater liquid dispensing conditions.
Smart Images

Figure CN119662234A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of guar gum fracturing fluid, and in particular relates to a cross-linking agent for improving the stability of guar gum fracturing fluid, a preparation method and the fracturing fluid. Background Art
[0002] In recent years, with the continuous deepening of unconventional reservoir exploration and development in my country, low-viscosity and high-viscosity slick water has become one of the main fracturing fluid systems due to its high drag reduction, suitability for complex fractures, and convenience for online mixing. However, from the perspective of on-site fracturing construction, the following problems still exist: the viscosity of high-viscosity slick water (drag reducer addition amount 0.5%-0.7%) does not exceed 20mPa·s, and the sand carrying effect is not good. A small amount of sand shedding often occurs during the high sand ratio continuous sand addition stage, resulting in the need to use continuous tubing to flush sand on the wellbore after fracturing, further extending the well handover cycle of the fracturing well and increasing the well construction cost; in addition, during the post-fracturing spraying, a large amount of unbroken polyacrylamide drag reducer macromolecules form a colloid with formation particles, proppants, crude oil and other substances, blocking the wellbore or spray nozzle, which is difficult to handle, and the unbroken drag reducer molecules are easy to be adsorbed on the formation surface, causing adsorption damage and affecting the fracturing transformation effect.
[0003] The concentration of thickener used in conventional guar gum fracturing fluid is high, which is not conducive to cost reduction and efficiency improvement. The concentration of guar gum used in conventional guar gum fracturing fluid is 0.45%-0.55%, and the residue content after fracturing fluid gel breaking is generally between 450-650 mg / L. Literature shows that the residue and filtrate cause a permeability loss rate of more than 20% to the fracture support zone and formation. Guar gum filter cake residue damages the supporting fractures and also increases material costs. The existing low-concentration guar gum fracturing fluid has poor hanging effect and poor temperature resistance. According to tests, under the condition of using clean water to prepare the fluid, the low-concentration (0.35%) guar gum fracturing fluid system provided by a domestic manufacturer has a low temperature resistance of 90°C and 170s -1 After 90 min of constant temperature shearing, the viscosity remained at 75 mPa·s; 120°C, 170s -1 After 90 minutes of constant temperature shearing, the viscosity is lower than 10mPa·s, and the temperature resistance is poor. The existing organoboron crosslinker in guar gum fracturing fluid is not suitable for low-concentration and ultra-low-concentration fracturing fluid systems. The huge difference in molecular size between guar gum thickener and organoboron crosslinker (the difference between the molecular length of the two is 9928.3 times, and the difference between the molecular diameter is 15.1 times) makes the crosslinker easily entrained by the thickener to form intramolecular crosslinking. The effective intermolecular crosslinking points are less than 1%, and one organoboron molecule crosslinks two guar gum molecules, which significantly affects the crosslinking efficiency. At a lower guar gum concentration (<0.35%), the crosslinking effect is extremely poor.
[0004] The ultra-low concentration guar fracturing fluid developed by Xi'an Shiyou University has a guar dosage of 0.25%, a temperature resistance of 90°C, and a core damage rate of less than 20%. A total of 402 wells have been constructed in Yanchang Oilfield. The ultra-low concentration guar fracturing fluid developed by Sinopec has a guar dosage of 0.30% and a temperature resistance of 90°C. The system has successfully carried out field tests in the Daniudi tight gas field. The ultra-low concentration guar fracturing fluid developed by Yanchang Oilfield has a guar dosage of 0.35% and a temperature resistance of 120°C. Domestic ultra-low concentration guar fracturing fluids still have problems of low viscosity and poor sand carrying capacity at high temperatures.
[0005] At present, there are few reports on ultra-low concentration guar gum fracturing fluid systems using seawater (mineralization value 30000mg / L-40000mg / L). For fracturing transformation of oil and gas wells near the sea, the use of seawater can save a lot of water fees and the cost of transporting clean water, which is conducive to cost control and efficiency improvement. However, the high concentration of high-valent metal ions such as calcium and magnesium in seawater seriously affects the free extension and adhesion of guar gum macromolecular chains in seawater, and the competitive cross-linking effect with the cross-linking agent molecules causes the cross-linking strength of the formed gel to be insufficient, which seriously affects its temperature resistance. These effects not only exist in conventional concentration guar gum fracturing systems, but are particularly significant in ultra-low concentration guar gum fracturing fluid systems. Summary of the invention
[0006] The present invention solves the technical problem by adopting the following technical solutions:
[0007] A seawater-based delayed crosslinking agent, wherein the seawater-based delayed crosslinking agent is a polyamine boron crosslinking agent, and the polyamine boron crosslinking agent is one of polyamine boron crosslinking agent I and polyamine boron crosslinking agent II;
[0008] The molecular structure of the polyamine boron crosslinking agent I is:
[0009]
[0010] The molecular structure of the polyamine boron crosslinking agent II is:
[0011]
[0012] Furthermore, the preparation method of the polyamine boron crosslinking agent I is:
[0013] S1. Put ethylene glycol and n-butanol into a reactor, add boric acid into the reactor while stirring, and heat to 110-130° C. under reflux;
[0014] S2, cooling the reaction mixture obtained in S1, adding tetraethylenepentamine, and then heating the reaction at 130-170° C. until a viscous yellow liquid is formed;
[0015] S3. Add polyol to the reaction mixture obtained in S2, heat at 130-170°C, cool, and treat to obtain polyamino boron crosslinking agent I.
[0016] Furthermore, in the preparation method of the polyamine boron crosslinking agent I, the molar ratio of ethylene glycol, n-butanol, boric acid, tetraethylene pentamine and polyol is:
[0017] (0.5-1.5):(0.4-0.6):(0.3-0.5):(0.06-0.10):(0.02-0.04).
[0018] Furthermore, the preparation method of the polyamine boron crosslinking agent II is:
[0019] S1, adding tris(2-aminoethyl)amine and anhydrous methanol to a reactor, separately mixing trimethyl borate and anhydrous methanol, and adding the mixed solution of trimethyl borate and anhydrous methanol to the reactor; wherein the molar ratio of tris(2-aminoethyl)amine to trimethyl borate is (0.05-0.20):(0.05-0.20);
[0020] S2. After the addition is completed, reflux at 110-130°C to obtain polyamino boron crosslinking agent II.
[0021] The seawater-based ultra-low concentration guar gum fracturing fluid obtained by using the above-mentioned seawater-based delayed crosslinking agent comprises, by mass fraction, 0.20%-0.35% of a plant gum thickener, 0.20%-0.40% of a seawater-based delayed crosslinking agent, 0.10%-0.30% of a seawater-based crosslinking enhancer, 0.05%-0.10% of a pH regulator, 0.05%-0.10% of a drainage aid, 0.2-3% of an anti-swelling agent, 0.03%-0.20% of a bactericide and the remainder of seawater.
[0022] Furthermore, the seawater-based cross-linking enhancer is one or a mixture of at least two of ethanolamine, diethanolamine, triethanolamine, sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and diethylenetriamine pentacarboxylate.
[0023] Furthermore, the plant gum thickener is hydroxypropyl guar gum.
[0024] Furthermore, the drainage aid is a fluorocarbon surfactant.
[0025] Furthermore, the anti-swelling agent is one or both of potassium chloride and dimethyldiallylammonium chloride.
[0026] Furthermore, the fungicide is one or a mixture of at least two of dodecyldimethylbenzyl ammonium chloride or isothiazolinones.
[0027] The advantages and positive effects of the present invention are:
[0028] (1) In the seawater-based ultra-low concentration guar gum fracturing fluid of the present invention, one cross-linking agent molecule has multiple cross-linking sites, which can generate intermolecular cross-linking with multiple guar gum molecules, reduce the probability of intramolecular cross-linking, and significantly improve the efficiency of intermolecular cross-linking. When using a lower concentration of guar gum, the cross-linked gel can achieve stronger viscoelasticity and rheology;
[0029] (2) The cross-linking enhancer used in the seawater-based ultra-low concentration guar gum fracturing fluid of the present invention can complex high-valent metal ions such as calcium and magnesium in seawater at relatively high concentrations, significantly reducing the influence of the above ions on the comprehensive performance of the ultra-low concentration guar gum fracturing fluid, especially the influence on the high temperature stability of the cross-linked gel;
[0030] (3) The amount of guar gum added in the seawater-based ultra-low concentration guar gum fracturing fluid of the present invention is 0.20%-0.35%, while the amount of guar gum added in the conventional guar gum fracturing fluid is usually 0.45%-0.55%, the amount of guar gum used is significantly reduced, and the content of residue after gel breaking is significantly reduced, which further reduces the damage of the residue to the reservoir, and the cost of the fracturing fluid is reduced by more than 30%;
[0031] (4) The present invention aims at the target wells for fracturing close to the sea, such as the Bohai Bay. The seawater-based ultra-low concentration guar gum fracturing fluid is prepared using the nearby seawater, which can not only save the cost of fresh water, but also save the freight for transporting fresh water, and the cost saving effect of fracturing fluid is particularly significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : is the viscosity-temperature curve diagram corresponding to Example 2 of the present invention;
[0033] Figure 2 3 is a viscosity-temperature curve corresponding to Example 3 of the present invention;
[0034] Figure 3 4 is a viscosity-temperature curve corresponding to Example 4 of the present invention;
[0035] Figure 4 It is the viscosity-temperature curve diagram corresponding to Comparative Example 1 of the present invention;
[0036] Figure 5 This is a fracturing construction curve diagram of the Qiye xx-xx well in Dagang Oilfield in an embodiment of the present invention. DETAILED DESCRIPTION
[0037] First, it should be noted that the specific structure, features and advantages of the present invention will be specifically described below by way of example, but all descriptions are only for illustration and should not be understood as limiting the present invention in any way. In addition, any single technical feature described or implied in the embodiments mentioned herein can still be combined or deleted between these technical features (or their equivalents) to obtain more other embodiments of the present invention that may not be directly mentioned herein.
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0039] Example 1
[0040] The seawater-based delayed crosslinking agent provided in this embodiment is a polyamine boron crosslinking agent, and the polyamine boron crosslinking agent is one of polyamine boron crosslinking agent I and polyamine boron crosslinking agent II;
[0041] The molecular structure of the polyamine boron crosslinking agent I is:
[0042]
[0043] The molecular structure of the polyamine boron crosslinking agent II is:
[0044]
[0045] The preparation method of the polyamine boron crosslinking agent I is:
[0046] S1. Add 0.5-1.5 mol ethylene glycol and 0.4-0.6 mol n-butanol to a round-bottom flask and a Dean Stark adapter equipped with a reflux condenser. Add 0.3-0.5 mol boric acid to the flask while stirring magnetically and heat to 110-130 °C under reflux until about 5 g of water is collected.
[0047] S2, cooling the reaction mixture to room temperature, and slowly adding 0.06-0.10 mol of tetraethylene pentamine, and then heating the reaction at 130-170° C. until a viscous yellow liquid is formed;
[0048] S3, adding 0.02-0.04 mol of polyol (sorbitol, pentaerythritol, dipentaerythritol or N-methylglucamine) to the reaction mixture, heating at 130-170° C. for 1 hour, cooling to room temperature, and treating with 10-50 mL of 50 wt.% sodium hydroxide solution to obtain a yellow liquid polyamino boron crosslinking agent I;
[0049] The reaction formula of the polyamine boron crosslinking agent I is as follows:
[0050]
[0051] The preparation method of the polyamine boron crosslinking agent II is:
[0052] S1. Add 0.05-0.20 mol of tris(2-aminoethyl)amine and 10-20 g of anhydrous methanol to a round-bottom flask, and add 0.05-0.20 mol of trimethyl borate and 6.88 g of anhydrous methanol to a pressure-equalizing addition funnel. While stirring evenly, add the mixture of trimethyl borate and anhydrous methanol dropwise to the round-bottom flask;
[0053] S2. After the addition is completed, reflux at 110-130°C for 6-10h to obtain a yellow liquid polyamine boron crosslinking agent II;
[0054] The reaction formula of the polyamine boron crosslinking agent II is:
[0055]
[0056] The seawater-based ultra-low concentration guar gum fracturing fluid obtained by using the above-mentioned seawater-based delayed crosslinking agent comprises, by mass fraction, 0.20%-0.35% of a plant gum thickener, 0.20%-0.40% of a seawater-based delayed crosslinking agent, 0.10%-0.30% of a seawater-based crosslinking enhancer, 0.05%-0.10% of a pH regulator, 0.05%-0.10% of a drainage aid, 0.2-3% of an anti-swelling agent, 0.03%-0.20% of a bactericide and the remainder of seawater.
[0057] Specifically, the seawater-based cross-linking enhancer is one or a mixture of at least two of ethanolamine, diethanolamine, triethanolamine, sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and diethylenetriamine pentacarboxylate; the plant gum thickener is hydroxypropyl guar gum; the pH adjuster is citric acid; the drainage agent is a fluorocarbon surfactant; the anti-swelling agent is one or two of potassium chloride and dimethyldiallylammonium chloride; the bactericide is one or a mixture of at least two of dodecyldimethylbenzylammonium chloride or isothiazolinone.
[0058] Example 2
[0059] This embodiment provides a seawater-based ultra-low concentration guar gum fracturing fluid, the preparation method of which comprises the following steps:
[0060] (1) Preparation of seawater-based delayed crosslinking agent:
[0061] S1. Add 1 mol ethylene glycol and 0.5 mol n-butanol to a round-bottom flask and a DeanStark adapter equipped with a reflux condenser. Add 0.4 mol boric acid to the flask while stirring magnetically and heat to 130 °C under reflux until about 5 g of water is collected.
[0062] S2, cooling the reaction mixture to room temperature, and slowly adding 0.08 mol of tetraethylene pentamine, and then heating the reaction at 150° C. until a viscous yellow liquid is formed;
[0063] S3. Add 0.03 mol of polyol (dipentaerythritol) to the reaction mixture, heat at 150°C for 1 hour, cool to room temperature, and treat with 30 mL of 50 wt.% sodium hydroxide solution to obtain a yellow liquid polyamine boron crosslinker I.
[0064] (2) Preparation of seawater-based ultra-low concentration guar gum fracturing fluid:
[0065] 400 mL of seawater (seawater mineralization is about 38000 mg / L) was measured by mass fraction, and 0.08% pH adjuster (citric acid), 0.08% drainage agent (fluorocarbon surfactant), 0.3% anti-swelling agent (dimethyldiallyl ammonium chloride), and 0.05% bactericide (isothiazolinone) were added respectively under the condition of stirring in Wu Yin mixer. After stirring for 5 minutes until uniform, 0.35% hydroxypropyl guar gum was added and stirred for 10 minutes until completely dissolved to form a base liquid; 0.20% seawater-based delayed crosslinking agent and 0.20% seawater-based crosslinking enhancer were slowly added to the base liquid while stirring to obtain a crosslinked gel.
[0066] The viscosity-temperature curve test method of the cross-linked gel is carried out in accordance with the Petroleum and Natural Gas Industry Standard SY / T5107-2016 "Water-Based Fracturing Fluid Performance Evaluation Method" of the People's Republic of China. Figure 1 It shows that the prepared gel is heated at 120℃ for 170s -1 After shearing for 90 minutes, the viscosity remains above 100mPa.s, meeting the on-site temperature resistance requirement of 120℃.
[0067] Example 3
[0068] The other steps are the same as those in Example 2, except that:
[0069] (1) Preparation of seawater-based delayed crosslinking agent In step S1, 1 mol of ethylene glycol was changed to 0.5 mol, 0.5 mol of n-butanol was changed to 0.4 mol, 0.4 mol of boric acid was changed to 0.3 mol, and 130°C was changed to 110°C; in step S2, 0.08 mol of tetraethylene pentamine was changed to 0.06 mol, and 150°C was changed to 130°C; in step S3, 0.03 mol of polyol (dipentaerythritol) was changed to 0.02 mol of polyol (N-methylglucamine), 150°C was changed to 130°C, and 30 mL 50 wt. % sodium hydroxide solution was changed to 10 mL; (2) in the preparation of seawater-based ultra-low concentration guar gum fracturing fluid, 0.08% pH adjuster (citric acid) was changed to 0.05%, 0.08% drainage aid (fluorocarbon surfactant) was changed to 0.05%, 0.3% anti-swelling agent (dimethyldiallyl ammonium chloride) was changed to 0.2%, 0.05% fungicide (isothiazolinone) was changed to 0.03%, 0.35% hydroxypropyl guar gum was changed to 0.20%, 0.20% seawater-based delayed crosslinking agent was changed to 0.30%, and 0.20% seawater-based crosslinking enhancer was changed to 0.10%.
[0070] The viscosity-temperature curve test method of the cross-linked gel is carried out in accordance with the Petroleum and Natural Gas Industry Standard SY / T5107-2016 "Water-Based Fracturing Fluid Performance Evaluation Method" of the People's Republic of China. Figure 1 The results show that the prepared gel was heated at 80℃ for 170s -1 After shearing for 50 minutes, the viscosity remains above 50mPa.s, meeting the on-site temperature resistance requirement of 80℃.
[0071] Example 4
[0072] The other steps are the same as those in Example 2, except that:
[0073] (1) Preparation of seawater-based delayed crosslinking agent In step S1, 1 mol of ethylene glycol was changed to 1.5 mol, 0.5 mol of n-butanol was changed to 0.6 mol, 0.4 mol of boric acid was changed to 0.5 mol, and 130° C. was changed to 120° C.; in step S2, 0.08 mol of tetraethylene pentamine was changed to 0.10 mol, and 150° C. was changed to 170° C.; in step S3, 0.03 mol of polyol (dipentaerythritol) was changed to 0.04 mol of polyol (sorbitol), 150° C. was changed to 170° C., and 30 mL of 50 wt.% sodium hydroxide solution was changed to 50 mL (2) In the preparation of seawater-based ultra-low concentration guar gum fracturing fluid, 0.08% pH adjuster (citric acid) was changed to 0.10%, 0.08% drainage aid (fluorocarbon surfactant) was changed to 0.10%, 0.3% anti-swelling agent (dimethyldiallyl ammonium chloride) was changed to 3% anti-swelling agent (potassium chloride), 0.05% fungicide (isothiazolinone) was changed to 0.20% fungicide (dodecyldimethylbenzyl ammonium chloride), 0.35% hydroxypropyl guar gum was changed to 0.30%, 0.20% seawater-based delayed cross-linking agent was changed to 0.40%, and 0.20% seawater-based cross-linking enhancer was changed to 0.30%.
[0074] The viscosity-temperature curve test method of the cross-linked gel is carried out in accordance with the Petroleum and Natural Gas Industry Standard SY / T5107-2016 "Water-Based Fracturing Fluid Performance Evaluation Method" of the People's Republic of China. Figure 1 It shows that the prepared gel is heated at 100℃ for 170s -1 After shearing for 90 minutes, the viscosity remains above 100mPa.s, meeting the on-site temperature resistance requirement of 100℃.
[0075] Comparative Example 1
[0076] A commercially available conventional organic boron crosslinking agent (provided by Inner Mongolia Chifeng Aolong Chemical Co., Ltd.) was used to replace the seawater-based delayed crosslinking agent in Example 2. The fracturing fluid was prepared according to the same steps and proportions as in Example 2 (2), and the water used for preparing the fluid was seawater.
[0077] The viscosity-temperature curve test method of the cross-linked gel is carried out in accordance with the Petroleum and Natural Gas Industry Standard SY / T5107-2016 "Water-Based Fracturing Fluid Performance Evaluation Method" of the People's Republic of China. Figure 1 It shows that the prepared gel is heated at 100℃ for 170s -1 After shearing for 35 minutes, the viscosity was lower than 50 mPa.s, indicating that the high-temperature rheological properties of the cross-linked fracturing fluid gel prepared by the commercially available conventional organic boron cross-linking agent were significantly lower than those of the seawater-based delayed cross-linking agent in Example 2.
[0078] Comparative Example 2
[0079] A commercially available conventional organic boron crosslinking agent (provided by Inner Mongolia Chifeng Aolong Chemical Co., Ltd.) was used to replace the seawater-based delayed crosslinking agent in Example 3. The fracturing fluid was prepared according to the same steps and proportions as in Example 3 (2), and seawater was used for preparing the fracturing fluid.
[0080] Comparative Example 3
[0081] A commercially available conventional organic boron crosslinking agent (provided by Inner Mongolia Chifeng Aolong Chemical Co., Ltd.) was used to replace the seawater-based delayed crosslinking agent in Example 4. The fracturing fluid was prepared according to the same steps and proportions as in Example 4 (2), and the water used for preparing the fluid was seawater.
[0082] In order to verify the performance difference comparison of the seawater-based ultra-low concentration guar gum fracturing fluid obtained in the above Examples 2, 3 and 4 and Comparative Examples 1, 2 and 3, the following relevant performance tests were carried out (after the base fluid viscosity and gel viscosity-temperature curve were tested in all the above Examples and Comparative Examples, 0.02% ammonium persulfate breaker was used to break the cross-linked gel at 90°C for 2h, and the resulting broken gel solution was subjected to relevant tests):
[0083] Table 1 Performance test of seawater-based ultra-low concentration guar gum fracturing fluid
[0084]
[0085] a Note: refers to the shear rate of 170s in high temperature and high pressure rheometer testing -1 , the viscosity tested at a shear time of 1.5h and a certain temperature is not less than 50mPa·s, and this temperature corresponds to the temperature resistance of the gel.
[0086] It can be seen from the experimental data analysis that the seawater-based ultra-low concentration guar gum fracturing fluid of the present invention has obvious advantages in comprehensive performance compared with the guar gum fracturing fluid prepared by using a conventional organic boron crosslinking agent. For example, the base fluid viscosity is stable (the viscosity of the base fluid of Example 2-4 does not change much compared with that of the just-made base fluid after being placed for 24 hours, while the viscosity of the base fluid corresponding to Comparative Example 1-3 is significantly reduced); the base fluid prepared with seawater has the characteristic of delayed crosslinking (the crosslinking time of Comparative Example 1-3 is extremely short and the crosslinking time cannot be adjusted); the jelly formed by Example 2-4 has good hanging property, while Comparative Example 1-3 basically cannot hang; in terms of temperature resistance, the jelly formed by Example 2-4 is generally 40-60°C higher than that of Comparative Example 1-3.
[0087] Field test of seawater-based ultra-low concentration guar gum fracturing fluid: The seawater-based fracturing fluid prepared with 0.35% (Example 2) and 0.20% (Example 3) guar gum was successfully tested in the Qiye xx-xx well of Dagang Oilfield. The sand ratio reached up to 30%, creating a new record of nearly 38000 mg / L of water salinity for the preparation of the fluid. See the attached fracturing construction curve for details. Figure 5 The water for preparing the solution is shown in Table 2 below:
[0088] Table 2 Water quality analysis of seawater used for liquid preparation
[0089]
[0090] The present invention is described in detail, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A seawater-based delayed crosslinking agent, characterized in that: The seawater-based delayed crosslinking agent is a polyamine boron crosslinking agent, and the polyamine boron crosslinking agent is one of polyamine boron crosslinking agent I and polyamine boron crosslinking agent II; The molecular structure of the polyamine boron crosslinking agent I is: The molecular structure of the polyamine boron crosslinking agent II is:
2. The seawater-based delayed crosslinking agent according to claim 1, characterized in that: The preparation method of the polyamine boron crosslinking agent I is: S1. Put ethylene glycol and n-butanol into a reactor, add boric acid into the reactor while stirring, and heat to 110-130° C. under reflux; S2, cooling the reaction mixture obtained in S1, adding tetraethylenepentamine, and then heating the reaction at 130-170° C. until a viscous yellow liquid is formed; S3. Add polyol to the reaction mixture obtained in S2, heat at 130-170°C, cool, and treat to obtain polyamino boron crosslinking agent I.
3. The seawater-based delayed crosslinking agent according to claim 2, characterized in that: In the preparation method of the polyamine boron crosslinking agent I, the molar ratio of ethylene glycol, n-butanol, boric acid, tetraethylene pentamine and polyol is: (0.5-1.5):(0.4-0.6):(0.3-0.5):(0.06-0.10):(0.02-0.04)。 4. The seawater-based delayed crosslinking agent according to claim 1, characterized in that: The preparation method of the polyamine boron crosslinking agent II is: S1, adding tris(2-aminoethyl)amine and anhydrous methanol to a reactor, separately mixing trimethyl borate and anhydrous methanol, and adding the mixed solution of trimethyl borate and anhydrous methanol to the reactor; wherein the molar ratio of tris(2-aminoethyl)amine to trimethyl borate is (0.05-0.20):(0.05-0.20); S2. After the addition is completed, reflux at 110-130°C to obtain polyamine boron crosslinking agent II.
5. A seawater-based ultra-low concentration guar gum fracturing fluid obtained by using the seawater-based delayed crosslinking agent according to claim 1, characterized in that: Measured by mass fraction, the fracturing fluid includes 0.20%-0.35% of plant gum thickener, 0.20%-0.40% of seawater-based delayed crosslinking agent, 0.10%-0.30% of seawater-based crosslinking enhancer, 0.05%-0.10% of pH regulator, 0.05%-0.10% of drainage aid, 0.2-3% of anti-swelling agent, 0.03%-0.20% of bactericide and the balance of seawater.
6. The seawater-based ultra-low concentration guar gum fracturing fluid according to claim 5, characterized in that: The seawater-based cross-linking enhancer is one or a mixture of at least two of ethanolamine, diethanolamine, triethanolamine, sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and diethylenetriamine pentacarboxylate.
7. The seawater-based ultra-low concentration guar gum fracturing fluid according to claim 5, characterized in that: The plant gum thickener is hydroxypropyl guar gum.
8. The seawater-based ultra-low concentration guar gum fracturing fluid according to claim 5, characterized in that: The degassing agent is a fluorocarbon surfactant.
9. The seawater-based ultra-low concentration guar gum fracturing fluid according to claim 5, characterized in that: The anti-swelling agent is one or two of potassium chloride and dimethyldiallyl ammonium chloride.
10. The seawater-based ultra-low concentration guar gum fracturing fluid according to claim 5, characterized in that: The bactericide is one or a mixture of at least two of dodecyldimethylbenzyl ammonium chloride or isothiazolinones.
Citation Information
Cited By
Low-concentration guanidine gum fracturing fluid suitable for high-salinity water solution preparation and application of low-concentration guanidine gum fracturing fluid
CN121064824A